2010
DOI: 10.3109/10641955.2010.525273
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Levels in Circulation and Breast Milk and mRNA Expression in Adipose Tissue of Preeclampsia Women

Abstract: PE women had a higher adiponectin concentration in the maternal blood as well as breast milk but lower adiponectin concentration in umbilical cord blood when compared to women with normal pregnancy. The elevated circulating adiponectin levels in PE women are probably because of a reduced degradation/elimination rather than an increased synthesis of this hormone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Results indicate no differences in insulin and leptin concentrations in colostrum regardless of the influence of the maternal gestational clinical condition, as previously demonstrated for diabetic [ 22 ] and smoking mothers [ 23 , 26 ]. On the other hand, increased adiponectin levels have been observed for hypertensive mothers in comparison to controls, as described by Liu et al [ 27 ]. Higher adiponectin serum and leptin levels in preeclampsia mothers have also been described by other authors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Results indicate no differences in insulin and leptin concentrations in colostrum regardless of the influence of the maternal gestational clinical condition, as previously demonstrated for diabetic [ 22 ] and smoking mothers [ 23 , 26 ]. On the other hand, increased adiponectin levels have been observed for hypertensive mothers in comparison to controls, as described by Liu et al [ 27 ]. Higher adiponectin serum and leptin levels in preeclampsia mothers have also been described by other authors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 64%
“…However, no such changes have been observed for leptin or other hormones [ 24 , 26 ]. Liu et al, assessed adiponectin concentrations in the breast milk of mothers presenting preeclampsia and observed increases when compared to controls [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ramsay et al [15] reported an elevation of plasma adiponectin concentration in women with PE compared with controls and suggested that adiponectin released during pregnancy could be a physiological response to minimize fat accumulation and also to decrease endothelial damage. However, Liu et al believed that circulating adiponectin levels in PE women might be due to a reduced degradation/elimination rather than an increased synthesis of this adipokine [31]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the consensus in the literature concerning the association between high maternal circulating leptin concentrations and preeclampsia, the evidence regarding maternal adiponectin concentrations in the presence of preeclampsia is inconsistent: higher [38][39][40][42][43][44]47,50,52,[139][140][141][142][143][144][145] , lower 28,[35][36][37][146][147][148][149][150] and similar adiponectin concentrations [151][152][153][154] have been reported in patients with preeclampsia compared to normal pregnant women (Table 4).…”
Section: Maternal Circulating Adiponectin and Complications Of Pregnancymentioning
confidence: 64%